Forward - Woldeyes, Yirga Gelaw (AuthorHouse, 2018)
In Education and Society in Africa, Germa Amare contributes to education and society in Ethiopia and beyond. In his examination of Ethiopian education in the 20th century, he looks at the impact of the church and of changes in government, incorporates valuable details on practices, and provides critical insights on the social function of education in African society. This collection lets us rethink how we may move forward in African education. "Dr Germa Amare was a colleague in the University of Lagos and I came to admire his cultured and scholarly approach, his academic integrity and his broad perspective on African education. He brings to his work a knowledge of African countries, which will be valuable to readers. I thoroughly commend his scholarly achievements and his work." Professor Emeritus Lalage Bown OBE, FRSE, FAcSS, Former Professor of Adult and Continuing Education, University of Glasgow, Scotland.